Difficulties of Undergraduate Students to Understand of 2nd Calculus - Ruslimin A; Masriyah Masriyah; Manuharawati Manuharawati (SAINTIS Publishing, 2019)
This study aims to describe the types of difficulties and factors causing the undergraduate students of Mathematics Education to have difficulty to understand materials of 2nd Calculus. This research is descriptive research with quantitative and qualitative approach. The research instruments used were tests and interview guides. The data analysis techniques consisted of three stages, namely: data reduction, data presentation and conclusions. The results of his research are the types of difficulties faced by students of S1 Mathematics Education in understanding 2nd Calculus lecture material, namely: Difficulties in the stage of understanding, Difficulties in the transformation phase, Difficulties in the process skills stage, Difficulties at the stage of writing answers / solutions and the factors that caused by intellectual factors, namely: students do not understand the integral concept of substitution, Students do not understand the concept of trigonometric comparisons, students do not understand how to make an integral substitution example and do the substitution substitution into an integral form whose solution is to be sought, students do not understand about decomposition in trigonometry and do not understand which one decomposes and which one decreases, students do not know the formulas commonly used in trigonometry.